Updated clinical and economic analysis of using follitropin alfa in combination with assisted reproductive technologies in 2022 - D. G. Shchurov; D. V. Blinov; N. V. Bashmakova; M. A. Polzikov; A. S. Semikhin (Фармакоэкономика, 2023)
Objective: to perform a clinical and economic analysis of using drugs containing follitropin alfa as an active substance and to assess the impact of the studied drugs on the budget of the state healthcare system of the Russian Federation considering cost data for 2022 in the population of women with infertility and poor ovarian response who are undergoing treatment with the use of assisted reproductive technologies (ART).Material and methods. Clinical and economic evaluation of follitropin alfa use in patients with infertility and poor ovarian response was performed by a cost minimization method, using data from the Uniform Information System for Procurement for the period from July to December 2022 inclusive. The budget impact analysis model compared the costs required for ovarian stimulation of patients with poor ovarian response receiving only a fixed dose combination (FDC) of follitropin alfa + lutropin alfa with the expected practice of switching 25% of these patients to follitropin alfa with a modeling time horizon of 1 year.Results. A cost analysis of an ovarian stimulation course using biosimilar follitropin alfa showed cost savings of 17% compared with the cost of therapy using the original follitropin alfa. Also, cost minimization analysis per cycle of ovarian stimulation demonstrated that the use of the biosimilar follitropin alfa was characterized by cost savings of 24,420 rubles (32.37%) compared to FCD of follitropin alfa + lutropin alfa. Compared to the 2021 data, in the current study based on 2022 data and including only biosimilar follitropin alfa, there was a 103% increase in savings. Budget impact analysis determined that switching 25% of the population from FCD of follitropin alfa + lutropin alfa to follitropin alfa would reduce direct medical costs by 17.3 million rubles (8.1%) per year. Savings in direct medical costs in the current study compared to 2021 increased by 117%.Conclusion. The clinical and economic analysis, as well as the budget impact analysis of using biosimilar follitropin alfa for ovarian stimulation in a population of women with infertility and poor ovarian response, confirm the economic expediency revealed in 2021. Moreover, according to 2022 data, the use of biosimilar follitropin alfa results in additional budgetary savings.